Vínculo socioafetivo entre o personal trainer e o idoso: a construção de um elo empático pelo cuidar - Torres, Cenyra Pimentel Cavalcanti (2022)
Population aging, added to the increase in the life expectancy of individuals, has caused changes in the demographic characteristics of Brazil. Therefore, this part of the population demands special attention, given the particularities of aging. Faced with this process, the caregiver appears in order to offer adequate attention and specific knowledge to deal with this phase of life, and as an emerging agent of this care, there is the Personal Trainer. Therefore, the objective of this study is to analyze how the socio-affective bond between the Personal Trainer and the elderly person is characterized, considering Personalized training. It consists of a descriptive study, which used the interview as an instrument. Based on the participants' narratives on the subject in question, a content analysis was carried out, according to Bardin. The instruments used were a semi-structured interview script, a voice recorder, and a computer for the transcription of the responses. The research was carried out in gyms in João Pessoa and the research participants were made up of elderly people aged over 60, practitioners of physical activity and who have had a bond of time, no less than twelve months, with the Personal Trainer who accompanies them and prescribe your workouts. It was concluded that the establishment of the empathic link between the elderly and Personal Trainers made it possible to develop a feeling of Personal acceptance, presenting itself as essential to understanding the other in its entirety. It was concluded that the establishment of the empathic link between the elderly and Personal Trainers made it possible to develop the feeling of Personal acceptance, presenting itself as essential to understanding the other in its entirety.